Ameliorative effects of Brassica oleracea var. viridis ethanol extract and fractions on cimetidine-induced reproductive toxicity in male Wistar rats - Ikuomola, Emmanuel Orire; Owu, Daniel Udofia; Oka, Victor Otu; Onaadepo, Olufunke; Ugwu, Felix Nnaemeka; Aja, Patrick Maduabuchi (Frontiers in Veterinary Science, 2025)
BackgroundMale infertility is a global health issue, with pharmaceutical agents such as cimetidine contributing significantly to gonadotoxicity through antiandrogenic and oxidative mechanisms. The search for natural protective agents has highlighted Brassica oleracea var. viridis (collard greens) for its antioxidant and endocrine-modulating properties.ObjectivesThis study evaluated the protective effects of Brassica oleracea var. viridis (collard greens) ethanol extract and its solvent fractions on cimetidine-induced reproductive toxicity in male Wistar rats, focusing on body/organ weights, hormonal profiles, antioxidant enzyme activities, and testicular histoarchitecture.MethodsThirty-five rats were divided into seven groups: control, cimetidine (120 mg/kg), ethanol extract (200 mg/kg), and cimetidine + fractions (aqueous, butanol, and hexane). After 8 weeks oral administration of extracts/fractions, sperm parameters, serum hormones (LH, FSH, and testosterone), oxidative stress markers (catalase, SOD, and MDA), and histopathology were assessed.ResultsCimetidine significantly reduce follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone levels (p < 0.05) while increasing oxidative stress, as evidenced by elevate malondialdehyde (MDA) superoxide dismutase (SOD) and catalase (CAT). It also caused distortion of the testicular architecture. Treatment with the ethanol extract (ELEBO) and solvent fractions restored hormonal balance and antioxidant activity. Histological analysis revealed preserved testicular architecture in treated groups compared to the degeneration observed in the cimetidine-induced group.ConclusionBrassica oleracea var. viridis exhibits significant protective effects against cimetidine-induced reproductive toxicity through hormonal regulation, antioxidative mechanisms, and tissue preservation. The ethanol extract of Brassica oleracea (ELEBO) showed the most potent activity, supporting its potential use as a therapeutic adjunct in male infertility linked to pharmaceutical exposures.